Simulasi Alat Produksi Limestone dan Silicastone Untuk Memenuhi Kebutuhan Pabrik Semen Existing dan Commissioning Pabrik Semen Indarung VI pada Semester II Tahun 2017 Di PT Semen Padang - Muhamad Irvan; Murad Murad; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT Semen Padang plans to commission their new cement factory, Indarung VI, which increases monthly demands for limestone and silica stone (supplied by existing Mine Area of Bukit Karang Putih) to 1.117.781 tones and 156.773 tones. This research is purposed to get the capability of production equipment (loaders, trucks, crushers, belt conveyors) in existing area to match production targets and to determine what kind of optimization is needed to make the equipment capable to fulfil the target. We approach this research by using a simulation that build based on actual conditions (operation pattern, effective working hours, and productivity), then comparing the result to the production targets. Optimizations are determined by analyzing effective hours and productivity of each equipment, then compare them to the theoretical ones. From the simulation, equipment in existing area has actual production of 674.503 tones limestone, and 81.960 ton silicastone, only 60% and 52% of the production targets. Therefore, optimization needs to be done. Optimization is doing by: improving the work efficiency from 69,90% to 86,11%; recalculate matching fleet; and adding two extra shifts per day. After implementing optimization into simulation, equipment in existing area finally, match production target, by producing 1.133.487 tones limestone and 162.471 tones silica stone.Keywords: Commissioning; Simulation; Optimization; Effective Hours; Productivity